Implementation of Islamic Trust and Moral Values ​​in Islamic Bank Frontliner Services - Aswin Fahmi Darma Darma; M. Guffar Harahap Guffar; Ami Nullah Marlis Tanjung Ami; Nur'ain Harahap Nur'ain (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2025)
The development of Islamic banking is marked not only by the expansion of financial services but also by the strengthening of Islamic values in service practices. This study is motivated by the gap between the ideal implementation of Sharia values and the actual performance of frontliners at BTPN Syariah, particularly concerning trustworthiness and Islamic ethics. The purpose of this research is to analyze the implementation of trust and ethical behavior in services and to evaluate their consistency in daily operational activities. This study employs a qualitative approach, using observation, interviews, and documentation, with validity ensured through triangulation. The findings indicate that trust is manifested through transparent information sharing, honesty in explaining products, and safeguarding customer confidentiality. Islamic ethics are evident in friendly, patient, and courteous interactions. However, challenges arise during peak hours, where information is often conveyed hurriedly. The novelty of this research lies in its focus on the spiritual and ethical dimensions of frontliner service, contrasting previous studies that primarily emphasized technical service aspects. The contribution of this study provides a strategic foundation for Islamic banks to strengthen an organizational culture grounded in Islamic values. Keywords: Trust; Morals; Frontliner Service; BTPN Syariah; Islamic Ethics